(untitled) (Global Journal of Science Frontier Research, 2019)
The physics of extreme states of matter (including dark matter) underlies the modern understanding of the evolution and structure of the Universe. The article presents the parameters of a new dark matter particle obtained in the experiments of Professor Attila Krashnahorkai during a bombardment of a piece of lithium-7 the protons with the formation of an unstable beryllium nucleus-8 and electrons -positrons pairs (fifth interaction). The article contains comments to the lecture of the Academician V.E. Fortova "The Physics of Extreme States of Matter.